Over 100 Million Frames per Second 368 Frames Global Shutter Burst CMOS Image Sensor with Pixel-wise Trench Capacitor Memory Array - Manabu Suzuki; Yuki Sugama; Rihito Kuroda; Shigetoshi Sugawa (Sensors, 2020)
In this paper, a prototype ultra-high speed global shutter complementary metal-oxide-semiconductor (CMOS) image sensor with pixel-wise trench capacitor memory array achieving over 100 million frames per second (fps) with up to 368 record length by burst correlated double sampling (CDS) operation is presented. Over 100 Mfps high frame rate is obtained by reduction of pixel output load by the pixel-wise memory array architecture and introduction of the burst CDS operation which minimizes the pixel driving pulse transitions. Long record length is realized by high density analog memory integration with Si trench capacitors. A maximum 125 Mfps frame rate with up to 368 record length video capturing was confirmed under room temperature without any cooling system. The photoelectric conversion characteristics of the burst CDS operation were measured and compared with those of the conventional CDS operation.